Reduction and the intracellular translocation of EphB2 in Tg2576 mice and the effects of β‐amyloid. Issue 6 (9th September 2013) - Qu, M.; Jiang, J.; Liu, X‐P.; Tian, Q.; Chen, L‐M.; Yin, G.; Liu, D.; Wang, J‐Z.; Zhu, L‐Q.
<x xml:space="preserve">Abstract</x> Aims EphB2 is a member of receptor tyrosine kinases (RTKs) family that is essential for the cell adhesion, neural crest migration, axon guidance and synaptogenesis in the nervous system. Recent studies show that preservation of EphB2 in a transgenic mouse model of Alzheimer's disease (AD) rescues the cognitive deficit, suggesting a crucial role of EphB2 in AD. However, the expression and distribution profiles of EphB2 in the early stage of AD have not been reported. Methods Immunohistochemistry, immunoblot and immunofluorescence were used to analyse the level of EphB2 in Tg2576 mice at different ages and in cultured neurones with Aβ treatment at different times. Results EphB2 was reduced in an age‐dependent manner in the olfactory bulb and the hippocampus of Tg2576 mice. The decrease of EphB2 appeared earlier in the olfactory bulb than the hippocampus, and reduction of EphB2 appeared earlier than that of MAP2, a dendritic cytoskeleton marker. In the cortex, EphB2 displayed a significant translocation from the neuronal processes to the cell bodies with ageing. In primary hippocampal neuronal cultures, Aβ42 treatment also induced the decrement of EphB2 that was prior to the decline of MAP2. Conclusions Our findings provide the first evidence for an age‐ and region‐dependent reduction and intracellular translocation of EphB2 in Tg2576 mice, and the foremost decrement of EphB2 in the olfactory bulb may represent an early sign of AD.